The Relationship between Knowledge and Attitude with Women Interest of Reproductive Age (WUS) to do Iva Test Examination in Loa Pari Village Working Area of Teluk in Puskesmas - Anggrea Diva Lestari; Dwi Hendriani; Nino Adib Chifdillah (Formosa Journal of Science and Technology, 2023)
Cervical cancer is the fourth most common type of cancer experienced by women. The IVA test is an easy, simple and capable screening method for cervical cancer lesion. Analyzing the relationship between the knowledge and attitude factors of WUS in Loa Pari. This study used a quantitative approach, analytic observational with a cross sectional design. The research sample totaled 105 WUS. Data collections was carried out by filling out questionnaires, with univariate, bivariete, and multivariate analysis. Based on the results of the study, statistical analysis using the Somer's D test showed that there was a relationship between knowledge (p-value = 0.000) and attitude (p-value = 0.001) with WUS interest in carrying out the IVA test. The Puskesmas is expected to increase the target, coverage and education about the IVA test for WUS in their working area. In this research, it can be concluded that there is a relationship between knowledge and attitudes with the interest of women of childbearing age (WUS) to carry out an IVA test.Suggestions in this study are that it is hoped that further research will be carried out regarding the relationship between knowledge and attitudes with the interest of women of childbearing age (WUS) to carry out an IVA test.